Five novel mutations of GALNS in Korean patients with mucopolysaccharidosis IVA12. Issue 3 (8th February 2013) - Park, Hyung‐Doo; Ko, Ah‐Ra; Ki, Chang‐Seok; Lee, Soo‐Youn; Kim, Jong‐Won; Cho, Sung Yoon; Kim, Se Hwa; Park, Sung Won; Sohn, Young Bae; Jin, Dong‐Kyu
Abstract Mucopolysaccharidosis IVA (MPS IVA; OMIM #253000) is caused by the deficiency of N‐acetylgalactosamine‐6‐sulfate sulfatase (GALNS), a lysosomal enzyme involved in the catabolism of keratan and chondroitin sulfate. In this study, we examined biochemical and genetic data from 6 Korean patients presenting with classic MPS IVA by measuring GALNS activity in peripheral blood leukocytes and skin fibroblasts. We initially identified Korean patients with MPS IVA by clinical, biochemical, and genetic analyses. We performed PCR‐direct sequencing to identify molecular defects of the GALNS gene in patients and assessed the mutational statuses of family members as well as 50 healthy unrelated subjects. In silico analyses were performed to check for novel mutations. The mean age of the six female patients was 8.0 ± 5.2 years (range: 2–17 years), and were all found to have severe reductions of GALNS enzyme. A total of 12 mutant alleles were identified, corresponding to 7 different mutations. Five novel mutations were c.218A>G (p.Y73C), c.451C>A (p.P151T), c.725C>G (p.S242C), c.752G>A (p.R251Q), and c.1000C>T (p.Q334X). Two other mutations were c.1156C>T (p.R386C) and c.1243‐1G>A. Two mutations, c.451C>A and c.1000C>T, accounted for 58% of all mutations in this sample. © 2013 Wiley Periodicals, Inc.